Sosialisasi Upaya Perlindungan Hukum Atas Hak-Hak Pasien dan Tenaga Medis di Puskesmas Sukamaju Kota Bandar Lampung - Eka Deviani; Yuniati, Ati; Kusworo, Daffa Ladro; Febbiazka, Karmilla (Nemui Nyimah, 2023)
Health law essentially provides legal certainty and protection, both for providers of health services and for recipients of health services, requiring a dynamic health law. For example, such as health workers who commit errors or negligence in carrying out their profession may be subject to disciplinary action determined by the Health Workers Disciplinary Council (Jo: Article 54 paragraphs 1 and 2 of Law No.23 of 1992 concerning health Jo. P No.32 of 1996 concerning health workers). Based on the results of a social approach to several communities in the inpatient health center of Sukamaju Village, East Bay Betung Subdistrict, Bandar Lampung City, they have never known the existence of Law No.36 of 2009 concerning Health, and do not understand about health services, patient protection, environmental health, health provision regulated in Law No.36 of 2009 concerning Health, so in this case socialization is needed as an effort to instill knowledge about the legal protection they have as patients. The methods considered relevant to achieve the above objectives are the lecture method and the discussion method, which are methods used to convey material about Law No.36 of 2009 concerning Health. The results showed that an understanding of the rights of patients and medical personnel in accordance with applicable legal procedures makes the community know what rights can be received based on the legal procedures in force.